Analisis Pajak Penghasilan Atas Transaksi Usaha E-Commerce di Kota Kupang - Rudi Megidius Wabang (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
This research aims to analyze the application of Income Tax (PPh) on E-Commerce business transactions in Kupang City. This research is a descriptive qualitative research with qualitative research type. The type of data used in this research is qualitative data, while the data sources come from primary data and secondary data. Data analysis was conducted using data analysis techniques based on Miles and Huberman. The results of the research show that the implementation of income tax (PPh) on E-Commerce businesses in the city of Kupang has not gone well because, up to now there is no separation or grouping of E-Commerce taxes and the majority of E-Commerce business actors have not registered their businesses online